2012
DOI: 10.1080/03079457.2012.667558
|View full text |Cite
|
Sign up to set email alerts
|

Distribution ofSalmonellaserovars and antimicrobial susceptibility ofSalmonellaEnteritidis from poultry in Zimbabwe

Abstract: A study was carried out to determine the distribution and antimicrobial susceptibility profiles of Salmonella serovars from chickens from large-scale commercial (LSC), small-scale commercial (SSC), and rural freerange (RFR) farms of Zimbabwe. Pooled cloacal swabs were collected for culture and isolation of Salmonella spp. A chi-square test was used to assess distribution differences of salmonellas among the farming sectors. Approximately 10% (283/2833) of the swabs were positive for Salmonella enterica, with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 32 publications
(37 reference statements)
1
10
2
2
Order By: Relevance
“…Equally of therapeutic significance is that, of the six antimicrobial agents used in the poultry industry in the Caribbean region, SXT was the most effective against the Salmonella isolates tested from the three countries, with only 11.9% exhibiting resistance. Makaya et al 1 (24) in a study in Zimbabwe reported a 0.0% prevalence of resistance to SXT. In the only published report on the antibiograms of Salmonella isolates from eggs (shells and contents) in the …”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Equally of therapeutic significance is that, of the six antimicrobial agents used in the poultry industry in the Caribbean region, SXT was the most effective against the Salmonella isolates tested from the three countries, with only 11.9% exhibiting resistance. Makaya et al 1 (24) in a study in Zimbabwe reported a 0.0% prevalence of resistance to SXT. In the only published report on the antibiograms of Salmonella isolates from eggs (shells and contents) in the …”
Section: Resultsmentioning
confidence: 97%
“…isolates by size o f farm' w -multiresistance patterns are known to vary and to reflect the use of antimicrobial agents in the respective poultry industries (15,19,24,25).…”
Section: Occurrence O F Resistance Among Salmonellamentioning
confidence: 99%
See 1 more Smart Citation
“…Son yıllarda dünya genelinde zoonotik gastrointestinal hastalıkların prevalansında dikkat çekici bir artış bildirilmektedir (2,24).…”
Section: Introductionunclassified
“…Kanatlı etlerinin tüketiminin artmasıyla tüm dünyada kanatlı kaynaklı zoonoz hastalıklarda bir artış görülmektedir. Salmonella serovarları kaynaklı infeksiyonlardaki artış genel olarak kanatlı etleri, yumurta içe-ren gıda ürünleri ve hayvan kaynaklı diğer gıda ürünleri-nin alımıyla ilişkilendirilmektedir (17,24). Kanatlılarda Salmonella türlerinin yüksek prevalansı nedeniyle AB'de tavuk sürüleri için (damızlık, yumurtacı ve broyler) kontrol programları uygulanmaktadır.…”
Section: Introductionunclassified